Vision-based 3D information modeling and applications - Ni, Yun (Nanyang Technological University, 2021)
We can infer the 3D structure of our surroundings simply by looking. It is long hoped that imaging devices can mirror such an ability, which is crucial to many computer vision tasks. This thesis is about our work on developing algorithms, as well as utilizing novel optical devices, in particular light-field cameras, to infer 3D information without active illuminations, and how such information can be used in various practical applications: